2015
DOI: 10.3389/fmars.2015.00026
|View full text |Cite
|
Sign up to set email alerts
|

Macroalgal responses to ocean acidification depend on nutrient and light levels

Abstract: Ocean acidification may benefit algae that are able to capitalize on increased carbon availability for photosynthesis, but it is expected to have adverse effects on calcified algae through dissolution. Shifts in dominance between primary producers will have knock-on effects on marine ecosystems and will likely vary regionally, depending on factors such as irradiance (light vs. shade) and nutrient levels (oligotrophic vs. eutrophic). Thus experiments are needed to evaluate interactive effects of combined stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 54 publications
3
67
2
Order By: Relevance
“…Under ocean acidification, an accumulation of phenolic compounds has been shown in phytoplankton (Jin et al., ) and macroalgae (Celis‐Plá, Hall‐ Spencer, Horta, & P, ), and this was also already observed in C. nodosa (J. Silva, M. M. Costa, I. Olivé, I. Barrote, M. Ruocco, C. Lauritano, G. Procaccini and R. Santos, in preparation). On the contrary, Arnold et al.…”
Section: Discussionmentioning
confidence: 66%
“…Under ocean acidification, an accumulation of phenolic compounds has been shown in phytoplankton (Jin et al., ) and macroalgae (Celis‐Plá, Hall‐ Spencer, Horta, & P, ), and this was also already observed in C. nodosa (J. Silva, M. M. Costa, I. Olivé, I. Barrote, M. Ruocco, C. Lauritano, G. Procaccini and R. Santos, in preparation). On the contrary, Arnold et al.…”
Section: Discussionmentioning
confidence: 66%
“…Therefore, seagrasses grown under elevated nutrient availability (usually a limiting resource66) often decrease the production of chemical defenses such as phenols6768. Being carbon-based compounds, most of the studies in terrestrial plants25 and some species of macroalgae69 have found increases in phenolic compounds with elevated CO 2 availability. Yet, because CO 2 is also a resource that can greatly limit primary production in seagrasses285270, we may expect a decrease in phenolics (rather than the increase often observed in terrestrial plants) under high CO 2 scenarios, following RAH.…”
Section: Discussionmentioning
confidence: 99%
“…Maximal non‐photochemical quenching (NPQ max ) was obtained from the tangential function of NPQ versus irradiance function (αNPQ) according to Eilers and Peeters (), following Celis‐Plá et al. ().…”
Section: Methodsmentioning
confidence: 99%